2023
DOI: 10.1001/jamanetworkopen.2023.39934
|View full text |Cite
|
Sign up to set email alerts
|

Treatments During Pregnancy Targeting ERBB2 and Outcomes of Pregnant Individuals and Newborns

Paul Gougis,
Beatriz Grandal,
Floriane Jochum
et al.

Abstract: ImportanceTargeted therapies directed against ERBB2 are the cornerstone of medical treatment for ERBB2-positive breast cancers but are contraindicated during pregnancy.ObjectivesTo describe the association of exposure to anti-ERBB2 agents during pregnancy with pregnancy and fetal or newborn outcomes, and to compare the risk and types of adverse outcomes reported more frequently in this context than after exposure to other anticancer agents.Design, Setting, and ParticipantsFor this case-control study, All repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…We found that individuals exposed to anti- ERBB2 drugs during pregnancy were at higher risk of oligohydramnios (ROR, 17.68; 95% CI, 12.26-25.52; P < .001), fetal or neonatal kidney failure (ROR, 9.15; 95% CI, 4.62-18.12; P < .001), and congenital respiratory malformations (ROR, 9.98; 95% CI, 2.88-34.67; P = .001), in line with previously published evidence, thus validating the use of VigiBase as a useful resource to investigate the association of pregnancy, fetal, and/or newborn outcomes with anticancer drugs. This study gave evidence for the risk of oligohydramnios provoked by fetal kidney insufficiency that could, in some rare cases, lead to respiratory tract malformations …”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…We found that individuals exposed to anti- ERBB2 drugs during pregnancy were at higher risk of oligohydramnios (ROR, 17.68; 95% CI, 12.26-25.52; P < .001), fetal or neonatal kidney failure (ROR, 9.15; 95% CI, 4.62-18.12; P < .001), and congenital respiratory malformations (ROR, 9.98; 95% CI, 2.88-34.67; P = .001), in line with previously published evidence, thus validating the use of VigiBase as a useful resource to investigate the association of pregnancy, fetal, and/or newborn outcomes with anticancer drugs. This study gave evidence for the risk of oligohydramnios provoked by fetal kidney insufficiency that could, in some rare cases, lead to respiratory tract malformations …”
Section: Introductionmentioning
confidence: 75%
“…In previous research using VigiBase, some of us performed a case-control disproportionality analysis to determine the reporting odds ratio (ROR) of pregnancy and/or fetal or newborn outcomes associated with exposure to anti- ERBB2 drugs compared with exposure to other anticancer drugs. 19 We found that individuals exposed to anti- ERBB2 drugs during pregnancy were at higher risk of oligohydramnios (ROR, 17.68; 95% CI, 12.26-25.52; P < .001), fetal or neonatal kidney failure (ROR, 9.15; 95% CI, 4.62-18.12; P < .001), and congenital respiratory malformations (ROR, 9.98; 95% CI, 2.88-34.67; P = .001), in line with previously published evidence, 20 , 21 thus validating the use of VigiBase as a useful resource to investigate the association of pregnancy, fetal, and/or newborn outcomes with anticancer drugs. This study gave evidence for the risk of oligohydramnios provoked by fetal kidney insufficiency that could, in some rare cases, lead to respiratory tract malformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, other reports present positive maternal outcomes after immunotherapy exposure [13][14][15]. Further reviews also suggest that targeted therapies (e.g., trastuzumab) in the first trimester are less likely to lead to complications [16], and their use during pregnancy might be possible under close monitoring [17], but the risk of pregnancy and foetal complications remains high [18]. Thus, standard treatments cannot be always given to pregnant cancer patients, reinforcing the difficulty of managing such patients.…”
Section: Introductionmentioning
confidence: 99%